Tata Laksana Oklusi Vena Retina Sentral - Elvira (PT Kalbe Farma Tbk., 2024)
Central retinal vein occlusion (CRVO) is a condition caused by retinal vein occlusion at the central or posterior of the optic nerve due to a thrombus. Risk factors are age, cardiovascular disease, and systemic disease. The incidence of CRVO in men and women is the same and most commonly occurs at the age of more than 50 years. The manifestation of decreased visual acuity in CRVO is associated with macula edema. Management of CRVO can be in the form of medication and arrest and modification of risk factors. Early detection and prompt treatment are important to preserve visual acuity.